Microtopographic correlations of vessels and roots of cranial nerves, provocating neuro-vascular compressive syndromes - Zozulya, Yu. P.; Trosh, R. M.; Fedirko, V. O.; Gudkov, V. V.; Onischenko, P. M.; Lisyany, O. M. (Ukrainian Neurosurgical Journal, 2010)
Syndromes of neurovascular compression or hyperactive disorder (SHD) of cranial nerves at most patients are provocated by vascular compression of corresponding nerve’s root. But some authors deny vascular compression to be the main etiological factor of SHD of cranial nerves and reveal plural contacts of vessels with nerves without those syndromes development. On the base of intraoperative investigation of neuro-vascular relationships it was found out that in the zone of real vascular compression nerve’s root decolouration was observed that meant capillary perfusion infringement and disappeared after decompression; as closer to 90° the pulsation vector according to nerve’s root in the place of contact than probability of SHD occurrence is higher and symptoms of corresponding syndrome are more expressed.